Pengaruh Metode Demonstrasi Terhadap Hasil Belajar Melukis Ekspresif Menggunakan Medium Sepatu Terhadap Siswa Kelas X SMK Negeri 9 Medan - Putra Halomoan Siregar; Sugito Sugito (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to prove the effect of using the demonstration method on the results of learning to expressive painting using shoes as a medium for class X students at SMK Negeri 9 Medan. This research uses a quasi experimental research method. With a sample of 66 class X students taken using cluster random sampling. This research used a control class (painting using conventional methods) and an experimental group (painting using demonstration methods). Based on the research results, the average pretest scores for the experimental and control classes were 61.48 and 61.27 and the average posttest scores for the experimental and control classes were 80.93 and 70.96. And it can be seen from the results of the t test where these results are marked with the t test value from the experiment, it was found that thit = 10.23, the price of ttab with dk = 62 with a real level of 0.05, it was obtained that ttab = 1.9989 with the result 10.23 > 1.9989. It can be concluded that there is a significant influence from the use of the demonstration method on the results of learning to paint using shoes as a medium for class X students at SMK Negeri 9 Medan.